Determinan Nilai Perusahaan pada Bank Umum Konvensional di Bursa Efek Indonesia Periode 2020-2021 - Sisca Santika (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2023)
This study uses the financial ratios CR, DER, and company size to identify the elements that affect business value. The Tobin's Q ratio is used to estimate the worth of a company. The Indonesia Stock Exchange's (IDX) annual report for the years 2020–2021 provided the information used in this analysis. Using a purposive sampling technique, the population of this study is the 42 conventional commercial banks that are listed on the Indonesia Stock Exchange for the 2020–2021 timeframe. Analysis is conducted using multiple linear regression. IBM SPSS 25 is the program used to process statistical data. The findings of this study offer empirical proof that the Current Ratio (CR), Debt to Equity Ratio (DER), and Firm Size all have an impact on a company's value. The Current Ratio (CR) partially has no impact on a company's value, while the Debt to Equity Ratio (DER) has a small but significant impact on a company's value.